Communication and Opinion Formation in a Medical Community: The Significance of The Detail Man - Rehder, Robert R. (Academy of Management Journal, 1965)
The article discusses interpersonal relations in communication and opinion formulation processes as evidenced in the pharmaceutical and medical industries. The article focuses on the detail man's r...